Possible linkages between Gamification and Constructivist Pedagogy - Fridrich, Máté (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Gamification (Fridrich, 2020, Deterding et al, 2011a; Deterding et al, 2011b) is one of the emerging systems for learning organization, assessment and motivation. However, in the absence of a commonly agreed definition and scientifically established criteria, its application in pedagogical practice is often ad hoc. To overcome this problem, our research is an integral part of the development of a complex gamification framework, which supports the pedagogical adaptation and application of gamification in Hungary and internationally by providing a clear set of criteria and definitions. As part of the grounding of the gamification model, the present study attempts to explore the possible interfaces between constructivism (Nahalka, 2002, 2013; von Glasersfeld, 1995), social constructivism (John-Steiner & Mahn, 1996; Palincsar, 1998; Vygotsky, 1978), the constructivist educational theory and gamification based on them. In our theoretical analysis, we will review the different approaches to constructivism and then, along the interpretative framework of gamification, we will explore the didactical and conceptual features that should be considered for integration in the subsequent development of a gamification framework.